Modification of breast cancer risk according to age and menopausal status: A combined analysis of five population-based case-control studies - Trentham-Dietz, Amy (2014)
PURPOSE: While several risk factors for breast cancer have been identified, studies have not consistently shown whether these factors operate more strongly at certain ages or for just pre- or postmenopausal women. We evaluated whether risk factors for breast cancer differ according to age or menopausal status. METHODS: Data from five population-based case-control studies conducted during 1988-2008 were combined and analyzed. Cases (N=23,959) and population controls (N=28,304) completed telephone interviews. Logistic regression was used to estimate adjusted odds ratios and 95% confidence intervals and tests for interaction by age and menopausal status. RESULTS: Odds ratios for first-degree family history of breast cancer were strongest for younger women—reaching two-fold elevations—but were still statistically significantly elevated by 58-69% among older women. Obesity was inversely associated with breast cancer among younger women and positively associated with risk for older women (interaction P<0.0001). Recent alcohol intake was more strongly related to breast cancer risk among older women, although consumption of 3 or more drinks/day among younger women also was associated with elevated odd ratios (P<0.0001). Associations with benign breast disease and most reproductive/menstrual factors did not vary by age. Repeating analysis stratifying by menopausal status produced similar results. CONCLUSIONS: With few exceptions, menstrual and lifestyle factors are associated with breast cancer risk regardless of age or menopausal status. Variation in the association of family history, obesity, and alcohol use with breast cancer risk by age and menopausal status may need to be considered when determining individual risk for breast cancer.